Single-stage Revision of Infected Tibia Nonunion with Antibiotic Cement-coated Intramedullary Nail versus Ilizarov Methods: A Systematic Review and Meta-analysis - Piercey, Joshua E; Noye, Nicholas; Muhib, Mohammad Atik; Tetsworth, Kevin (Journal of limb lengthening & reconstruction, 2025)
The objective of this study was to perform a meta-analysis evaluating rates of infection clearance in single stage revision of infected tibial non-union with antibiotic cement coated intramedullary nailing (ACCIN) compared to Ilizarov external fixation methods. A systematic review was performed of the Medline, Embase, and Cochrane databases to identify relevant articles. Eligibility criteria included studies of adult patients, written in the English language, with cohorts and outcomes clearly stated. The primary outcome measure was clinical resolution of infection; secondary outcomes included bony union and management of bone loss. This study was conducted adhering to the PRISMA guidelines. The Cochrane ROBINS-I tool was used to assess bias of the included studies, and funnel plots were created to assess study heterogeneity. A total of sixteen papers (n=331 cases) reporting the outcomes of single stage treatment of infected tibial non-unions were identified and reviewed according to the selection criteria stipulated above. Ten utilizing Ilizarov external fixation methods (n=242 cases) and six utilizing antibiotic cement coated intramedullary nails (ACCIN) (n=89 cases) were included in the final analysis. Mean age, sex, time to follow-up, clinical resolution of infection, and union rate were analysed for heterogeneity using Cochran's Q statistic, the I-square test, and two-way ANOVA analysis of means. Included studies in both cohorts were homogeneous for sex, resolution of infection, and union rate. These variables where further analysed with Chi Squared crosstab and weighted means analysis. No significant differences were identified in the rate of successful resolution of infection or bony union when comparing the single-stage Ilizarov method (93.8%, 87.6%) to the single-stage ACCIN (87.6%, 82.0%) (P=0.193, P =0.065). The time, resource, and convenience benefits of single stage limb reconstruction procedures for infected non-union of the tibia are only advantageous if eradication of infection and bone union are consistently achieved. This meta-analysis suggests that treatment of infected tibial non-unions using single-stage debridement achieves comparable clinical control of infection, regardless of whether the limb is stabilized by insertion of antibiotic cement coated intramedullary nails or if instead stabilized in concert with Ilizarov methods. These results indicate ACCIN should be considered non-inferior to Ilizarov methods when used in singlestage protocols in these challenging cases. However, for tibial bone defects > 2cm Ilizarov methods may be more likely to achieve union and simultaneously eradicate infection.